Pengaruh Literasi Keuangan, Perilaku Keuangan dan Persepsi Risiko terhadap Pinjaman Online: Studi Kasus Generasi Milenial dan Generasi Z di Jawa Barat - Serafica Dhara Ayuandika; Aldi Akbar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
As a result of increased accessibility to information and technological advancements, online loans are becoming more popular among Millennials and Generation Z. There are substantial financial dangers associated with taking out loans online. Individuals' choices to use these services are greatly influenced by their level of financial knowledge, their financial behavior, and their perception of risk. The purpose of this research is to get a better understanding of young people's financial habits and risk management strategies by examining the impact of these three variables on online loan use in West Java. By sending out surveys to 250 people who have taken out loans online, this study uses a quantitative approach. Using SPSS, we conducted hypothesis tests (t-test, f-test, and coefficient of determination), testing for validity and reliability, multiple linear regression, and tests for classical assumptions. Those who are more informed about personal finance are more likely to exercise caution while taking out loans online, suggesting that financial literacy plays a key role in this relationship. Respondents that exhibit responsible financial habits are better equipped to handle the complexities of taking out loans online. People who are aware of the dangers are more likely to exercise caution while using these services, demonstrating how perceptions of risk influence decision-making.